Collective migration of cancer‐associated fibroblasts is enhanced by overexpression of tight junction‐associated proteins claudin‐11 and occludin. Issue 2 (8th November 2013) - Karagiannis, George S.; Schaeffer, David F.; Cho, Chan-Kyung J.; Musrap, Natasha; Saraon, Punit; Batruch, Ihor; Grin, Andrea; Mitrovic, Bojana; Kirsch, Richard; Riddell, Robert H.; Diamandis, Eleftherios P.
Abstract : It has been suggested that cancer‐associated fibroblasts (CAFs) positioned at the desmoplastic areas of various types of cancer are capable of executing a migratory program, characterized by accelerated motility and collective configuration. Since CAFs are reprogrammed derivatives of normal progenitors, including quiescent fibroblasts, we hypothesized that such migratory program could be context‐dependent, thus being regulated by specific paracrine signals from the adjacent cancer population. Using the traditional scratch assay setup, we showed that only specific colon cancer cell lines (i.e. HT29) were able to induce collective CAF migration. By performing quantitative proteomics (SILAC), we identified a 2.7‐fold increase of claudin‐11, a member of the tight junction apparatus, in CAFs that exerted such collectivity in their migratory pattern. Further proteomic investigations of cancer cell line secretomes revealed a specific signature, involving TGF‐β, as potential mediator of this effect. Normal colonic fibroblasts stimulated with TGF‐β exerted myofibroblastic differentiation, occludin (OCLN) and claudin‐11 (CLDN11) overexpression and cohort formation. Subsequently, inhibition of TGF‐β attenuated all the previous effects. Immunohistochemistry of the universal tight junction marker occludin in a cohort of 30 colorectal adenocarcinoma patients defined a CAF subpopulation expressing tight junctions. Overall, these data suggest that cancer cells may induce CLDN11 overexpression and subsequent collective migration of peritumoral CAFs via TGF‐β secretion. Highlights: We showed that cancer cell conditioned media (HT29) causes collective fibroblast migration. We demonstrated that this migratory pattern is associated with the myofibroblastic phenotype. We demonstrated that this migratory pattern is occludin‐ and claudin‐11‐mediated. We demonstrated that occludin and claudin‐11 are regulated by TGF‐beta. We showed clinical/immunohistochemical relevance of our data using a cohort of CRC patients.